ὑστερέω and πίστις Χριστοῦ in Romans 3:23 A Response to Steven Enderlein - Porter, Stanley E. 1956-; Cirafesi, Wally V.; Enderlein, Steven E. (2013)
This article is a response to Steven Enderlein on the translation of Rom 3:23 and its implications for the πίστις Χριστοῦ debate. While affirming Enderlein's suggestion that the verb ὑστερέω is better understood as "lack" rather than "fall short," we argue against his conclusions (1) that this translation leads to a subjective genitive reading of πίστις Χριστοῦ in Rom 3:22, 26; and (2) that the verb alludes to the early Jewish theology of Adam in Paul's day and thus should be read in view of the Adam/Christ contrast in Rom 5. We suggest that rendering ὑστερέω as "lack" in fact has no direct linguistic bearing on Paul's use of πίστις Χριστοῦ; however, this rendering of ὑστερέω does influence interpretation of Rom 3:23-24 because of its relation to other words that share its semantic domain.
Keywords: Paul; Romans; Pistis Christou; hysteréo; Greek Language; Translation